Effect of live yeast on performance of piglets - Dias, L.; Dullius, J. L.; Cella, P. S. (Scientific Electronic Archives, 2017)
Antibiotics are traditional growth promoters for pigs, aimed at improving animal performance. However, their widespread use in animal diets has been questioned due to the risk of toxicity and endanger human health, and may also cause problems of bacterial resistance to antibiotics. This resulted in a search for substitutes additives such as probiotics base of live yeast (Saccharomyces cerevisiae) that are able to colonize the gut, keeping your balance and creating a barrier against pathogenic microorganisms, and thus improve animal performance. Given the above, the objective of this study is to evaluate the effect of probiotic live yeast on the performance parameters of piglets in the nursery phase. The experiment was conducted in the swine industry, Universidade Tecnológica Federal do Paraná, Campus Dois Vizinhos. Crusaders 18 piglets were used 50 days old and weighing 12 kg, distributed in a completely randomized design containing two treatments (T1 - basal diet without inclusion of enhancers efficiency and T2 - basal diet + 0.2% addition of probiotic). The probiotic used in food as a source of T2 has the live yeast Saccharomyces cerevisiae. The animals were subjected to 7 days of adaptation, this time receiving the basal diet. Feed intake, feed conversion, weight gain, economic viability and stool consistency were evaluated. Performance data submitted to analysis of variance, and the difference between the observed average by F test. Just feed intake showed a statistical difference (P <0.05) where the diet containing the probiotic (T2) showed a lower consumption. Thus it can be concluded that the use of live yeast are positively influenced the economic and productive performance of piglets. Â